A game theory model applied to the program: young people building the future in Mexico - Garrido, Aletsy Alvarado; Lases, Santiago Romero (Revista Internacional de Salarios Dignos, 2023)
Unemployment and poverty rates have impacted society in recent years, especially in the most vulnerable population. Governments have established programs that try to eradicate these problems. In this case, this work focuses on analyze, based on the game theory methodology, a viable option that allows the contract of the “Jóvenes Construyendo el Futuro” program to be made official, giving a new possibility of insertion into the labor market to the interns. The results obtained show that the Nash equilibrium is found when the company decides to formalize the contract that was previously had, and the intern decides to accept. This taking into account 2 conditions; that the company offers a balanced salary, and the intern provides production that meets the expectations established by the company. The study was oriented towards the identification and solution of the aforementioned problems, focusing particularly on poverty and unemployment. The general goal was to design effective measures that contribute to the progressive eradication of these socioeconomic challenges.